Procedure placement using temporal ordering information - Gloy, Nikolas; Blackwell, Trevor; Smith, Michael D.; Calder, Brad (Proceedings of the 30th annual ACM/IEEE international symposium on Microarchitecture, 1997)
Instruction cache performance is very important to instruction fetch efficiency and overall processor performance. The layout of an executable has a substantial effect on the cache miss rate during execution. This means that the performance of an executable can be improved significantly by applying a code-placement algorithm that minimizes instruction cache conflicts. We describe an algorithm for procedure placement, one type of code-placement algorithm, that significantly differs from previous approaches in the type of information used to drive the placement algorithm. In particular, we gather temporal ordering information that summarizes the interleaving of procedures in a program trace. Our algorithm uses this information along with cache configuration and procedure size information to better estimate the conflict cost of a potential procedure ordering. We compare the performance of our algorithm with previously published procedure-placement algorithms and show noticeable improvements in the instruction cache behavior.